"Dominant" Myelolipoma Encasing Adrenal Cortical Carcinoma: An Unusual Variation of Myelolipoma Occurring as a Synchronous and Predominant Neoplasm. (December 2014) - Wang, Jayson; Fisher, Cyril; Thway, Khin
Although myelolipomas of the adrenal glands are detected with increasing frequency with advances in imaging, the occurrence of myelolipoma with adrenal cortical carcinoma remains very rare. We present a case of combined myelolipoma with adrenal cortical carcinoma in a 47-year-old man. In previously reported cases of adrenal cortical carcinoma and myelolipoma, the latter occurred as incidental foci within or peripheral to the carcinoma, perhaps representing "myelolipomatous metaplasia" rather than true neoplasia. We describe a new finding, in which the myelolipomatous component consisted of a large mass adjacent and dominant to the carcinoma. The presence of these 2 defined and apparently independent tumors suggests, in this case, the occurrence of collision or synchronous neoplastic events, rather than of metaplasia.